2021
DOI: 10.3389/fphys.2021.757857
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Measurement of Pulmonary Gas Exchange Efficiency: The Oxygen Deficit

Abstract: The efficiency of pulmonary gas exchange has long been assessed using the alveolar-arterial difference in PO2, the A-aDO2, a construct developed by Richard Riley ~70years ago. However, this measurement is invasive (requiring an arterial blood sample), time consuming, expensive, uncomfortable for the patients, and as such not ideal for serial measurements. Recent advances in the technology now provide for portable and rapidly responding measurement of the PO2 and PCO2 in expired gas, which combined with the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Q mismatch [11]. This O 2 deficit has been shown indeed to strongly correlate with the conventional A-aDO 2 in hypoxemic patients [12] and in healthy volunteers exercising in a hypoxic environment [13].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Q mismatch [11]. This O 2 deficit has been shown indeed to strongly correlate with the conventional A-aDO 2 in hypoxemic patients [12] and in healthy volunteers exercising in a hypoxic environment [13].…”
Section: Introductionmentioning
confidence: 79%
“…In particular, we identified that the inaccuracy (i.e., the increase in cPaO 2 -mPaO 2 difference) of the measurement was independently associated with the difference between PaCO 2 and PETCO 2 . This statistical relationship may partially explain some errors in the estimated PaO 2 , as the algorithm of the AGM100, considering the Bohr effect, corrects the cPaO 2 using the PETCO 2 [10,11]. Measurement of PETCO 2 in healthy people breathing a hypoxic mixture has been shown to be highly reproducible and can be considered as a reliable surrogate of PaCO 2 [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations